SENSORY EVALUATION, SHELFLIFE AND NUTRITIONAL COMPOSITION OF BREADNUT (ARTOCARPUS CAMANSI) COOKIES - Go, Marivel B.; Velos, Severina V.; Minyamin, Antonieta V.; Bagsit, Rosita D.; Pableo, Romeo G. (Journal of Agriculture and Technology Management, 2018)
Despite its being nutritious and potential uses and food, breadnut (Artocarpus camansi) remains underutilized. This study aimed to develop breadnut products for its extensive use and specifically aimed to determine the acceptability of chocolate cookies formulated from the mixtures of breadnut seed flour and all purpose flour and the shelf life of the most acceptable cookie  formulation.  The  cookies  were  prepared  in  different  ratios  of  all  purpose  flour  and breadnut seed flour in percent (0:100, 25:75, 50:50, 75:25, 100:0) with 100 percent all purpose flour served as the control. The five formulations were evaluated by the 50 consumers as to color, odor, crispiness, flavor and general acceptability using descriptive 9-point Hedonic scale. And the most acceptable cookies were evaluated for storage quality which was done for six (6) months to determine its shelf life. Results showed that all formulated breadnut cookies were acceptable, scoring 6.5 based on the 9-point hedonic scale.   The cookie with 50 percent BSF was the most acceptable based on general acceptability score. There were no significant (p< 0.05) differences on the sensory properties being tested to the cookies made from BSF up to 75 percent. The formulated cookies have significant amount of nutrients needed by the body.   It is safe with guaranteed desirable sensory properties for six (6) months. It is recommended for consumption and commercialization.